The Factors Affecting Financial Performance of Listed Real Estate Firms : Evidence from West Malaysia” - Chan, Chia Wen (Universiti Malaysia Sarawak (UNIMAS), 2014)
The top 20 high financial performance real estate firms that been broadcasted in REHDA 2013 booklet found that not all the firms are listed in Bursa Malaysia. This motivated the paper study to examine the factors affecting financial performance of firms for 11 years starting from 2002 until 2012. This paper employed financial ratios as dependent variable in index form while free cash flow, firm size and leverage ratio as independent variables. SPSS system has been used to analyse and calculate comprehensive financial performance index. Besides, E-views 5 is used to analyse the relationship between index, free cash flow, firm size and leverage ratio. While STATA is used to reconfirm the statistical results obtained. Findings observed that free cash flow and firm size is positive significant to comprehensive financial performance index, while leverage is negative significant to comprehensive financial performance index.